Significance of organic and inorganic fertilizers in maintaining soil fertility and increasing crop productivity in Ethiopia: a review - Tamirat Wato; Tilahun Negash; Alemu Andualem; Amare Bitew (Environmental Research Communications)
Ethiopia’s economy has been significantly influenced by agriculture. However, it is unable to feed the nation’s expanding population. One of the most significant obstacles to improving food production in Ethiopia is the declining soil fertility. Various development measures, including the intensification of agriculture using contemporary agricultural technologies, have been implemented to enhance the underwhelming performance of agriculture. One of the contemporary agricultural technologies introduced into Ethiopian agriculture is fertilizer, which helps smallholder farmers produce more effectively. Although there was a focus on promoting the use of these newly introduced technologies, exploratory findings showed that many farmers did not do so. Hence, this study aimed to review the different effects of organic and inorganic fertilizers on soil fertility and crop production, as well as their economic role in the country, specifically, the importance and value of organic and inorganic fertilizers, the significance of organic fertilizer application to enhance crop production, and the constraints of organic and inorganic fertilizers that affect farmers or users. Regarding soil health, balancing the use of organic and inorganic fertilizers can be beneficial for soil health and sustainable agriculture. Incorporating organic matter through composting and manure application improves soil structure and fertility over time, while judicious use of synthetic fertilizers can provide targeted nutrient supplementation when needed. Additionally, employing practices such as crop rotation, cover cropping, and soil conservation measures can further enhance soil health and minimize environmental impacts and as a result, it can optimize yields of crops.